Prevalence and clinical features of carotid artery web in patients undergoing endovascular thrombectomy for acute ischemic stroke - Chi-Ting Chung; Chih-Hao Chen; Yen-Heng Lin; Chang-Jie Cheng; Hai-Jui Chu; Chuan-Hsiu Fu; Kuo-Wei Chen; Chung-Wei Lee; Sung-Chun Tang; Jiann-Shing Jeng (Journal of the Formosan Medical Association)
Purpose: Carotid artery web (CaW) is a rare focal fibromuscular dysplasia that can lead to embolic strokes with large vessel occlusion. This condition can be effectively treated with endovascular thrombectomy (EVT). Our study aims to assess the prevalence of CaW among patients with acute ischemic stroke (AIS) who underwent EVT and to compare the clinical characteristics of CaW with other carotid artery pathologies. Methods: We enrolled consecutive patients with AIS who underwent EVT at a single medical center and two regional teaching hospitals in Taiwan from September 2014 to December 2021. We compared CaW with carotid dissection (CaD) and carotid large artery atherosclerosis (CaLAA) in terms of patient demographics and thrombus histological findings. Results: Of the 576 AIS patients who underwent EVT, four (mean age: 50 years) were diagnosed with CaW, resulting in a prevalence of 0.69%. Among these four patients, three experienced successful reperfusion after EVT and achieved functional independence (defined as a modified Rankin Scale score ≤2) three months post-stroke. Importantly, none of the CaW patients suffered a recurrent stroke within one year. Patients with CaW were younger than those with CaD or CaLAA, and exhibited fewer vascular risk factors. Additionally, CaW was associated with distal occlusion sites. The thrombus composition in CaW patients was similar to that in CaD patients. Conclusion: In conclusion, CaW is a rare finding among Asian patients with carotid artery disease who undergo for AIS. It is more prevalent in younger patients with a limited number of vascular risk factors.